POTENTIAL FOR ESTABLISHING REGIONAL CYBER-PHYSICAL SYSTEMS AS A NEW CLUSTER MODEL FOR TOURISM DEVELOPMENT - Anna Polukhina; Vladimir Lezhnin (Proceedings on Engineering Sciences, 2024)
The regions of the Volga Federal District have experienced a notable increase in tourism and recreation indicators in recent years. These indicators include the emergence of new collective accommodation facilities, the establishment of tourism clusters and the development of their digital infrastructure, the emergence of modern national digital services and platforms in the tourism industry, an increase in effective demand, etc. The paper aims to analyse the administration of the local systems in the Volga Federal District, which represent a new model of cluster establishment. It also analyses the key indicators of tourism and recreation in various regions. In the context of Industry 4.0 and the digital transformation of the tourism sector, the setting up of local cyber-physical systems is suggested as the main strategy for local system development. The primary strategy and mechanisms for enhancing the development of the tourism sector in the Volga Federal District are outlined in this research. The paper provides, among others, quantitative and qualitative indicators of the development of local systems in the Volga Federal District's tourism industry; local tourism systems are examined from the perspective of the cluster approach.